Incidence and factors associated with newly implemented do‐not‐attempt‐resuscitation orders among deteriorating patients after rapid response system activation: A retrospective observational study using a Japanese multicenter database - Tatsuya Tsuji; Yoshiki Sento; Toshiyuki Nakanishi; Tetsuya Tamura; Eisuke Kako; Izumi Sato; Koji Kawakami; Tatsuya Kawasaki; Takaki Naito; Shigeki Fujitani; Kazuya Sobue (Acute Medicine & Surgery, 2023)
Abstract Aim The rapid response system (RRS) was initially aimed to improve patient outcomes. Recently, some studies have implicated that RRS might facilitate do‐not‐attempt‐resuscitation (DNAR) orders among patients, their families, and healthcare providers. This study aimed to examine the incidence and factors independently associated with DNAR orders newly implemented after RRS activation among deteriorating patients. Methods This observational study assessed patients who required RRS activation between 2012 and 2021 in Japan. We investigated patients’ characteristics and the incidence of new DNAR orders after RRS activation. Furthermore, we used multivariable hierarchical logistic regression models to explore independent predictors of new DNAR orders. Results We identified 7904 patients (median age, 72 years; 59% male) who required RRS activation at 29 facilities. Of the 7066 patients without pre‐existing DNAR orders before RRS activation, 394 (5.6%) had new DNAR orders. Multivariable hierarchical logistic regression analyses revealed that new DNAR orders were associated with age category (adjusted odds ratio [aOR], 1.56; 95% confidence interval, 1.12–2.17 [65–74 years old reference to 20–64 years old], aOR, 2.56; 1.92–3.42 [75–89 years old], and aOR, 6.58; 4.17–10.4 [90 years old]), malignancy (aOR, 1.82; 1.42–2.32), postoperative status (aOR, 0.45; 0.30–0.71), and National Early Warning Score 2 (aOR, 1.07; 1.02–1.12 [per 1 score]). Conclusion The incidence of new DNAR orders was one in 18 patients after RRS activation. The factors associated with new DNAR orders were age, malignancy, postoperative status, and National Early Warning Score 2.